Improving the Prevention and Control of Newcastle Disease in Birds - Ismailovich, Saydaliyev Dilshod; Jaxongirovna, Shapulatova Zumrat; Raxmatullaevich, Raximov Odilbek; o‘g‘li, Bobomurodov Rustam Ismoil (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides information on Newcastle disease in birds, its pathogenesis, epizootiology, the use of various vaccines to improve disease prevention and control measures, testing the immunogenic activity of the vaccine in the serum of vaccinated birds in response to hemagglutination, in poultry an analysis of the results of determining the strength of the generated immunity is given.